2020
DOI: 10.26434/chemrxiv.12053535.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of Aptamers Targeting Receptor-Binding Domain of the SARS-CoV-2 Spike Glycoprotein

Abstract: The World Health Organization has declared the outbreak of a novel coronavirus (SARS-CoV-2 or 2019-nCoV) as a global pandemic. However, the mechanisms behind the coronavirus infection are not yet fully understand, nor are there any targeted treatments or vaccines. In this study, we identified high-binding-affinity aptamers targeting SARS-CoV-2 RBD, using an ACE2 competition-based aptamer selection strategy and a machine learning screening algorithm. The K<sub>d</sub> values of the optimized CoV2-RB… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 35 publications
2
80
0
Order By: Relevance
“…This charge distribution will create a speci c resistivity of the intrinsic silicon channel. While it has been reported [17] and proven by the response of the TFT sensor that the aptamer binds to the spike protein, what is unknown is the exact binding location of the protein and how the local charge distribution of the protein is arranged. The observed effect could be explained if the presence of the protein were to limit or shield the effect of the charges on the aptamer, while not adding any additional charge contribution of its own.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This charge distribution will create a speci c resistivity of the intrinsic silicon channel. While it has been reported [17] and proven by the response of the TFT sensor that the aptamer binds to the spike protein, what is unknown is the exact binding location of the protein and how the local charge distribution of the protein is arranged. The observed effect could be explained if the presence of the protein were to limit or shield the effect of the charges on the aptamer, while not adding any additional charge contribution of its own.…”
Section: Resultsmentioning
confidence: 99%
“…An aptamer that was previously reported to bind to the spike protein of the COVID-19 virus was used [17]. The sequence is 5'-CAGCACCGACCTTGTGCTTTGGGAGTGCTGGTCCAAGGGCGTTAATGGACA-3'.…”
Section: Methodsmentioning
confidence: 99%
“…Animal and human coronaviruses evolve to acquire the same host receptors and attachment factors and overcome the interspecies barrier from animals to human. Specifically, S glycoprotein interaction with its binding receptor determines host tropism, pathogenicity and therapeutic clues [ 80 ]. CoVs recognize multiple host receptors via distinct S domains.…”
Section: Covs Infection Of Human Hostsmentioning
confidence: 99%
“…MHV S1 protein also evolutionarily acquired murine CEACAM1a-recognizing activity [ 102 ]. Therefore, CoVs are under evolution to adapt their host receptor interaction to infect cross-species hosts [ 80 , 103 ]. On the host side, to escape the lethal pressure from CoV infections, hosts have also evolved to acquire SA-binding proteins such as siglecs to inhibit or activate the innate immune cells.…”
Section: Covs Infection Of Human Hostsmentioning
confidence: 99%
“…Song et al have developed new aptamers targeting S protein of SARS-CoV-2 and particularly receptor binding domain (RBD). The authors reported K d values of 5.8 and 19.9 nM for CoV2-RBD-1C and CoV2-RBD-4C DNA aptamers respectively ( Song et al, 2020 ). The aptamers needs to be further evaluated for their ability to interfere and disrupt binding between host ACE2 and RBD of spike protein both in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%